Migrant Child Labour of Western Odisha in India: An Analytical Study - Nanda, Samir Kumar (Middle Eastern Journal of Research in Education and Social Sciences, 2020)
Purpose: The aim of this study is to analyze the status of migrant child laborers in all the ten districts of Western Odisha in India. Identification of the area of concentration of migrant child labor in Western Odisha and evaluations of dimensions of the problem has been made in this article. Approach/Methodology/Design: In this study descriptive qualitative research method is applied. The population of the research was the innocent migrant child laborers and their parents of Western Odisha .Total sampling technique was used in this study. The sample consisted of eighty migrant child laborers that had migrated to Andhra Pradesh and were rescued by the author with the help of Labor & Employment Department, Government of Odisha, Government of Andhra Pradesh, and Andhra Pradesh Police. Findings: The result of the study indicates that due to acute poverty, illiteracy of children and their parents, low family income and big family size, people have migrated from one state to another state with their family members and children in search of works and higher wages. It is also found out that children are forced to work in hazardous occupations like brick kilns instead of going to schools. Moreover, it can be stated that the lack of awareness and non-implementation of Labour Laws are also among the main reasons for the prevalence of child labour. Practical Implications: The research study contributes to the understanding of the causes, consequences and remedies of child labor problems in the society. The results will provide solutions to the stakeholders to integrate the victims of child labor for the betterment of their lives. Originality/value: The study explores the impact of the child labor system on the society. Certain possible solutions are suggested to make Western Odisha, Odisha as well as the whole country, free from child labor practices.